Physiological and behavioral differences in sensory processing: a comparison of children with Autism Spectrum Disorder and Sensory Modulation Disorder - Schoen, Sarah A.; Miller, Lucy J.; Brett-Green, Barbara A.; Nielsen, Darci M. (Frontiers in Integrative Neuroscience, 2009)
A high incidence of sensory processing difficulties exists in children with Autism Spectrum Disorder (ASD) and children with Sensory Modulation Disorder (SMD). This is the first study to directly compare and contrast these clinical disorders. Sympathetic nervous system markers of arousal and reactivity were utilized in a laboratory paradigm that administered a series of sensory challenges across five sensory domains. The Short Sensory Profile, a standardized parent-report measure, provided a measure of sensory-related behaviors. Physiological arousal and sensory reactivity were lower in children with ASD whereas reactivity after each sensory stimulus was higher in SMD, particularly to the first stimulus in each sensory domain. Both clinical groups had significantly more sensory-related behaviors than typically developing children, with contrasting profiles. The ASD group had more taste/smell sensitivity and sensory under-responsivity while the SMD group had more atypical sensory seeking behavior. This study provides preliminary evidence distinguishing sympathetic nervous system functions and sensory-related behaviors in Autism Spectrum Disorder and Sensory Modulation Disorder. Differentiating the physiology and sensory symptoms in clinical groups is essential to the provision of appropriate interventions.